1980
DOI: 10.1002/cber.19801130539
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylierung substituierter Pyrrole

Abstract: N‐Acetylation of Substituted Pyrroles Using dimethylaminopyridine a method is presented which allows to transform substituted pyrroles into the N‐acetates in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Accordingly, the tricyclic tertiary alcohol 5 was synthesized very efficiently in three steps from indole ( 7 ; Scheme ). Although initial experiments showed that, unlike the smooth amidation of an aliphatic amine with an acyclic anhydride, the reaction of indole ( 7 ) and succinic anhydride ( 8 ) was slow, which can possibly be attributed to the weak nucleophilicity of the indole amine2, 11 and the increased stability of cyclic anhydride 8 . We found that the desired indole carboxylic acid 11 could be obtained in quantitative yield by heating a combination of Et 3 N and a catalytic amount of 4‐dimethylaminopyridine (DMAP) as base in dichloromethane at reflux.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the tricyclic tertiary alcohol 5 was synthesized very efficiently in three steps from indole ( 7 ; Scheme ). Although initial experiments showed that, unlike the smooth amidation of an aliphatic amine with an acyclic anhydride, the reaction of indole ( 7 ) and succinic anhydride ( 8 ) was slow, which can possibly be attributed to the weak nucleophilicity of the indole amine2, 11 and the increased stability of cyclic anhydride 8 . We found that the desired indole carboxylic acid 11 could be obtained in quantitative yield by heating a combination of Et 3 N and a catalytic amount of 4‐dimethylaminopyridine (DMAP) as base in dichloromethane at reflux.…”
Section: Methodsmentioning
confidence: 99%
“…4.5.1.6 Acylation Several useful procedures for N-acylation of pyrroles are available, for example by acyl transfer from 1-acetylimidazole, which offers an efficient route to 1-acetylpyrrole [282]. Alternative attractive methods for N-acylation rely on the use of acetic anhydride [283], or acyl chlorides in the presence of and triethylamine and DMAP as the catalyst [284]. Exposure of pyrroles to di(tert-butyl)dicarbonate in the presence of DMAP in acetonitrile solution gives access to many useful 1-(tert-butoxycarbonyl) pyrroles in high yields [285].…”
Section: Nitrationmentioning
confidence: 99%
“…To avoid this type of side-product, it was obvious that the NH function of 1 had to be protected, but this turned out to be difficult because standard methods for introduction of amino-protective groups such as Boc ( tert -butoxycarbonyl), originally applied in peptide synthesis, did not give satisfactory results with pyrroles. Influenced by a paper by Bohlmann et al, in which the authors acetylated a number of pyrroles and indoles in 73-91% yields with a small excess of acetic anhydride in the presence of 1 equiv of DMAP at room temperature , we decided to attempt to make Boc-pyrrole with di- tert -butyl dicarbonate (Boc 2 O) along a similar line. In this context we developed an optimized procedure to such Boc compounds based on the use of a catalytic amount of DMAP without extra base, which was subsequently applied also for the synthesis of N in -Boc-protected tryptophan and peptides thereof …”
Section: Introductionmentioning
confidence: 99%